Rush : Expositie actuele kunst. - Campens, Angelique (Oudenaarde : Stad Oudenaarde, 2004)
Clinckx, Christine ; Cole, Stijn ; De Decker, Koen ; Dheedene, Stefaan ; Fauconnier, Hilde ; Van Ingelgom, Ignace ; Musgrave, Christopher ; Pacquée, Ria ; Schepens, Steve ; Spie, Merlin ; Tahon, Johan ; Turck, Marianne ; Volckaert, Tim ; Woestenborghs, Tom
Nederlands
Exhibition. Rush. Kapel Van Maagdendale Oudenaarde. Stad Oudenaarde. 11.09.2004 - 10.10.2004
boek